Magnesium aluminate spinel transparent ceramic and preparation method thereof
Through vacuum hot pressing process and thermal isostatic pressure treatment of high and low pressure cyclic pressure, the problem of poor uniformity and easy cracking of large-size magnesium aluminum spinel transparent ceramics is solved, and large-size and high-uniform ceramic preparation is achieved.
Patent Information
- Application Number
- CN202411859360.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult to prepare large-size, crack-free magnesium-aluminum spinel transparent ceramics, and have poor uniformity.
The vacuum hot pressing process of high and low pressure cyclic pressing combined with the step-by-step cooling and in-situ annealing process of hot isostatic pressure. Through vacuum hot press sintering and hot isostatic pressure treatment, ceramic cracking is avoided and large-size and high uniformity magnesium-aluminum spinel transparent ceramic preparation is achieved.
It effectively avoids ceramic cracking, improves the uniformity and density of large-sized ceramics, and obtains large-sized and high-uniformity magnesium-aluminum spinel transparent ceramics.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of transparent ceramic materials, and in particular to a magnesium-aluminum spinel transparent ceramic and a preparation method thereof. Background Art
[0002] Magnesium aluminum spinel (MgAl2O4) transparent ceramics have excellent properties such as high melting point, high transmittance, wide transmission band, high hardness, high strength, high thermal conductivity, good thermal shock resistance, corrosion resistance and high temperature resistance. They can be widely used in infrared guidance windows, fairings of high Mach aircraft, transparent armor and optoelectronic equipment windows in extreme environments. With the development of equipment, magnesium aluminum spinel transparent ceramics are required to have large size and high uniformity.
[0003] At present, the preparation methods of magnesium-aluminum spinel transparent ceramics mainly include vacuum hot pressing / hot isostatic pressing and vacuum sintering / hot isostatic pressing. Although vacuum sintering / hot isostatic pressing can prepare fine-grained ceramics with high mechanical properties, it has particularly high requirements for raw material powders, and generally requires a particle size of no more than 50nm. In addition, when this method is used to prepare large-sized magnesium-aluminum spinel transparent ceramics, due to the increase in the weight of the sample, the friction between the sample and the carrier will cause the sintering shrinkage to be hindered, and deformation and cracking will occur, making it difficult to obtain large-sized, crack-free samples. Vacuum hot pressing is a simultaneous process of forming and densification, which promotes particle rearrangement and pore removal through axial pressure. It has the characteristics of low sintering temperature, short time, and effective control of green body deformation, and is more suitable for the preparation of large-sized magnesium-aluminum spinel transparent ceramics. However, in the preparation process of large-sized transparent ceramics, due to the large size, if the process control is not appropriate, problems such as poor uniformity and cracking are prone to occur, making it difficult to obtain large-sized, highly uniform samples. Summary of the invention
[0004] The purpose of this application is to provide a magnesium-aluminum spinel transparent ceramic and a preparation method thereof, so as to obtain a large-sized and highly uniform magnesium-aluminum spinel transparent ceramic, and solve the problem of poor uniformity and easy cracking of large-sized transparent ceramics. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a method for preparing a magnesium-aluminum spinel transparent ceramic, which comprises the following steps:
[0006] S1. Raw material pretreatment, comprising: adding a sintering aid and an organic solvent to a magnesium aluminum spinel powder for ball milling, and then spray granulating to obtain a magnesium aluminum spinel spherical powder with an average particle size of 20-150 μm, wherein the mass percentage of the sintering aid is 0-0.5% based on the mass of the magnesium aluminum spinel powder, and the mass percentage of the organic solvent is 50-400%;
[0007] S2. Vacuum hot pressing, comprising: vacuum hot pressing and sintering the spherical powder of magnesium aluminum spinel, the vacuum degree is 10-1 -10 -3 Pa, sintering temperature is 1300-1600℃, high pressure is 35-50MPa, low pressure is 15-25MPa, high and low pressure cycle pressurization is performed 2-8 times, high pressure insulation time is 10-30min, low pressure insulation time is 10-30min, and the total sintering time is 2-6 hours; pressure is released, the pressure is reduced to 0, and the temperature is reduced to 200-400℃ at a cooling rate of 2-5℃ / min, and then to room temperature to obtain a magnesia-alumina spinel sintered body;
[0008] S3. Hot isostatic pressing, comprising: in an argon atmosphere, the temperature is 1600-1800°C, the pressure is 150-200MPa, the magnesium-aluminum spinel sintered body is kept hot and pressurized for 1-5 hours, then the temperature is reduced to 1100-1400°C at a cooling rate of 1-2°C / min, the temperature is kept for 5-20h for in-situ annealing, and then the temperature is reduced to room temperature at a cooling rate of 3-5°C / min to obtain the magnesium-aluminum spinel transparent ceramic.
[0009] The second aspect of the present application provides a magnesium-aluminum spinel transparent ceramic prepared according to the preparation method provided in the first aspect of the present application.
[0010] The present application provides a magnesium-aluminum spinel transparent ceramic and a preparation method thereof, wherein the preparation method comprises S1. raw material pretreatment, S2. vacuum hot pressing, including high-low pressure cyclic pressing; and S3. hot isostatic pressing. The present application adopts a vacuum hot pressing process with high-low pressure cyclic pressing combined with a step-by-step cooling and in-situ annealing process of hot isostatic pressing, which can effectively avoid ceramic cracking and realize the preparation of large-size, high-uniformity magnesium-aluminum spinel transparent ceramics.
[0011] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0012] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0013] The first aspect of the present application provides a method for preparing a magnesium-aluminum spinel transparent ceramic, which comprises the following steps:
[0014] S1. Raw material pretreatment, comprising: adding a sintering aid and an organic solvent to a magnesium aluminum spinel powder for ball milling, and then spray granulating to obtain a magnesium aluminum spinel spherical powder with an average particle size of 20-150 μm, wherein the mass percentage of the sintering aid is 0-0.5% based on the mass of the magnesium aluminum spinel powder, and the mass percentage of the organic solvent is 50-400%;
[0015] S2. Vacuum hot pressing, comprising: vacuum hot pressing and sintering the spherical powder of magnesium aluminum spinel, the vacuum degree is 10 -1 -10 -3 Pa, sintering temperature is 1300-1600℃, high pressure is 35-50MPa, low pressure is 15-25MPa, high and low pressure cycle pressurization is performed 2-8 times, high pressure insulation time is 10-30min, low pressure insulation time is 10-30min, and the total sintering time is 2-6 hours; pressure is released, the pressure is reduced to 0, and the temperature is reduced to 200-400℃ at a cooling rate of 2-5℃ / min, and then to room temperature to obtain a magnesia-alumina spinel sintered body;
[0016] S3. Hot isostatic pressing, comprising: in an argon atmosphere, the temperature is 1600-1800°C, the pressure is 150-200MPa, the magnesia-alumina spinel sintered body is kept hot and pressurized for 1-5 hours, then cooled to 1100-1400°C at a cooling rate of 1-2°C / min (i.e., the first cooling rate), kept for 5-20h for in-situ annealing, and then cooled to room temperature at a cooling rate of 3-5°C / min (i.e., the second cooling rate) to obtain the magnesia-alumina spinel transparent ceramic.
[0017] In step S1, the average particle size of the magnesium aluminate spinel spherical powder can be, for example, 20 μm, 30 μm, 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 130 μm, 150 μm or a range consisting of any two of these values; if the average particle size of the magnesium aluminate spinel spherical powder is too high, for example, higher than 150 μm, it is not conducive to improving the transparency of the magnesium aluminate spinel transparent ceramics; if it is too low, for example, lower than 20 μm, it is not conducive to the densification of the magnesium aluminate spinel transparent ceramics. Based on the mass of the magnesium aluminate spinel powder, the mass percentage of the sintering aid can be, for example, 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two of the values therein, and the mass percentage of the organic solvent can be, for example, 50%, 80%, 100%, 120%, 150%, 180%, 200%, 250%, 300%, 350%, 400% or a range consisting of any two of the values therein.
[0018] In step S2, the sintering temperature can be, for example, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, or a range consisting of any two of the values; the high pressure can be, for example, 35MPa, 38MPa, 40MPa, 43MPa, 45MPa, 50MPa, or a range consisting of any two of the values; the low pressure can be, for example, 15MPa, 17MPa, 20MPa, 23MPa, 25MPa, or a range consisting of any two of the values; the number of high and low pressure cycles can be, for example, 2 , 3, 4, 5, 6, 7, 8 or a range consisting of any two of them; the high pressure holding time can be, for example, 10min, 15min, 20min, 25min, 30min or a range consisting of any two of them; the low pressure holding time can be, for example, 10min, 15min, 20min, 25min, 30min or a range consisting of any two of them; the total sintering time can be, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or a range consisting of any two of them. The cooling rate can be, for example, 2℃ / min, 2.5℃ / min, 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min or a range consisting of any two of them; the temperature dropped to, for example, can be 200℃, 250℃, 300℃, 350℃, 400℃ or a range consisting of any two of them.
[0019] In step S3, the temperature of the insulation and pressure holding can be, for example, 1600°C, 1650°C, 1700°C, 1750°C, 1800°C, or a range consisting of any two of the values therein; the pressure of the insulation and pressure holding can be, for example, 150MPa, 155MPa, 160MPa, 165MPa, 170MPa, 175MPa, 180MPa, 185MPa, 190MPa, 195MPa, 200MPa, or a range consisting of any two of the values therein; and the time of the insulation and pressure holding can be, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a range consisting of any two of the values therein. The first cooling rate may be, for example, 1°C / min, 1.5°C / min, 2°C / min, or a range consisting of any two of these values, the temperature of the in-situ annealing may be, for example, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or a range consisting of any two of these values, and the holding time of the in-situ annealing may be, for example, 5h, 6h, 8h, 10h, 12h, 15h, 18h, 20h, or a range consisting of any two of these values. The second cooling rate may be, for example, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, or a range consisting of any two of these values.
[0020] The preparation method of magnesium-aluminum spinel transparent ceramics provided in the present application adopts vacuum hot pressing with high and low pressure cyclic pressurization. In the low pressure stage, the grains slide and the pores are eliminated. In the high pressure stage, the ceramics are densified. Through multiple cycles of high and low pressures, the uniformity and density of large-size ceramics can be significantly improved. Hot isostatic pressing post-treatment can improve the transparency of the ceramics. The hot isostatic pressing cooling process adopts step-by-step cooling and in-situ annealing processes, which can effectively avoid ceramic cracking and reduce thermal stress, thereby solving the problem of easy cracking of large-size ceramics and obtaining large-size, high-uniformity magnesium-aluminum spinel transparent ceramics.
[0021] In some embodiments, the ball milling includes a ball milling speed of 50-200 rpm (r / min) and a ball milling time of 0.5-5 hours. The ball milling speed can be, for example, 50 rpm, 100 rpm, 150 rpm, 200 rpm, or a range consisting of any two of the values, and the ball milling time can be, for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a range consisting of any two of the values.
[0022] In some embodiments, the purity of the magnesium-aluminum spinel powder is ≥99.9%; preferably, the purity of the magnesium-aluminum spinel powder is ≥99.99%; more preferably, the purity of the magnesium-aluminum spinel powder is ≥99.999%. The present application can avoid the influence of other impurities and improve the transmittance performance of magnesium-aluminum spinel transparent ceramics by regulating the purity of the magnesium-aluminum spinel powder within the above range.
[0023] In some embodiments, the particle size D50 of the magnesia-alumina spinel powder is 0.1-2 μm. The particle size D50 of the magnesia-alumina spinel powder can be, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, or a range consisting of any two of these values.
[0024] In some embodiments, the high and low pressure cycles are performed 2-6 times.
[0025] In some embodiments, the sintering aid is selected from at least one of Y2O3, La2O3, LiF, NaF, CaO, and MgF2. The present application adopts the above sintering aid to reduce the hot pressing temperature and improve the transmittance performance of the magnesium aluminum spinel transparent ceramic.
[0026] In some embodiments, the organic solvent is selected from at least one of anhydrous ethanol and isopropanol.
[0027] In some embodiments, step S2 includes placing the magnesium aluminum spinel spherical powder into a mold for vacuum hot pressing and sintering. The present application has no particular limitation on the mold, as long as the purpose of the present application can be achieved, for example, the mold is a graphite mold.
[0028] The second aspect of the present application provides a magnesium-aluminum spinel transparent ceramic prepared according to the preparation method provided in the first aspect of the present application.
[0029] In some embodiments, the magnesium-aluminum spinel transparent ceramic is a round piece with a diameter of Φ400mm-800mm, or a square piece with a length of 400mm-600mm and a width of 400mm-600mm; the thickness of the magnesium-aluminum spinel transparent ceramic is 5mm-20mm.
[0030] In some embodiments, the transmittance of the magnesium aluminum spinel transparent ceramic is 81-85%.
[0031] Example
[0032] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0033] Test methods and equipment:
[0034] Size test: Use a vernier caliper to test the size of the magnesium aluminum spinel transparent ceramic.
[0035] Transmittance test: Fourier transform infrared spectrometer (NEXUS 670), refer to the standard "JC / T 2020-2010 Test method for transmittance of translucent fine ceramics" for evaluation, and obtain the transmittance of magnesium aluminum spinel transparent ceramics at a wavelength of 3μm.
[0036] Uniformity test: Through the transmittance test, the transmittance of the magnesium-aluminum spinel transparent ceramic at 5 positions was measured, and the range of the transmittance at different positions was calculated. The range ≤1% indicates that the magnesium-aluminum spinel transparent ceramic has good uniformity.
[0037] Integrity test: Use a 5x magnifying glass to visually observe the magnesium aluminum spinel transparent ceramic.
[0038] Example 1-1
[0039] S1. Raw material pretreatment: The homemade magnesium aluminum spinel powder with a purity of ≥99.99% and a D50 of 1.0 μm was added with a sintering aid LiF and an organic solvent anhydrous ethanol for ball milling. The ball milling speed was 100 rpm and the ball milling time was 2 hours. The mixed slurry was granulated by a pressure spray granulator to obtain a magnesium aluminum spinel spherical powder with an average particle size D50 of 80 μm, wherein the mass percentage of the sintering aid M1 was 0.2% based on the mass of the magnesium aluminum spinel powder, and the mass percentage of the organic solvent M2 was 300%;
[0040] S2. Vacuum hot pressing: The spherical powder of magnesium aluminum spinel is loaded into a graphite mold and placed in a vacuum hot pressing sintering furnace for vacuum hot pressing sintering. The vacuum degree is 10 -2 Pa, sintering temperature is 1400℃, high and low pressure cycle pressurization method is adopted: high pressure is 40MPa, low pressure is 20MPa, high and low pressure cycle pressurization is performed 3 times, high pressure insulation time is 20min, low pressure insulation time is 20min, total sintering time is 2 hours, pressure sintering is completed; pressure is released, pressure is reduced to 0, temperature is reduced to 300℃ at a cooling rate of 3.5℃ / min, and then naturally cooled to room temperature to obtain a magnesia-alumina spinel sintered body;
[0041] S3. Hot isostatic pressing: The magnesia-alumina spinel sintered body is placed in a hot isostatic pressing furnace under an Ar atmosphere at a temperature of 1700°C and a pressure of 175MPa for 3 hours, then cooled to 1250°C at a rate of 1.5°C / min, kept for 12 hours for in-situ annealing, and then cooled to room temperature at a rate of 4°C / min to obtain magnesia-alumina spinel transparent ceramics.
[0042] Example 1-2 to Example 1-7
[0043] Except that in step S2, the corresponding preparation parameters are adjusted according to Table 1, the rest is the same as Example 1-1.
[0044] Example 2-1 to Example 2-9
[0045] Except that in step S1, the corresponding preparation parameters are adjusted according to Table 2, the rest is the same as Example 1-1.
[0046] Example 3-1 to Example 3-7
[0047] Except that in step S3, the corresponding preparation parameters are adjusted according to Table 3, the rest is the same as Example 1-1.
[0048] Comparative Example 1-1
[0049] Except that step S2 adopts the steps shown below, the rest is the same as Example 1-1;
[0050] S2. The spherical powder of magnesium aluminum spinel is loaded into a graphite mold and placed in a vacuum hot pressing sintering furnace for vacuum hot pressing sintering. The vacuum degree is 10 -2 Pa, the sintering temperature is 1400°C, and the sintering is carried out at a pressure of 30MPa for 2 hours; the pressure is released, the pressure is reduced to 0, the temperature is lowered to 300°C at a cooling rate of 3.5°C / min, and then the temperature is naturally lowered to room temperature to obtain a magnesia-alumina spinel sintered body.
[0051] Comparative Example 1-2
[0052] Except that in step S2, the corresponding preparation parameters are adjusted according to Table 1, the rest is the same as Example 1-1.
[0053] Table 1
[0054] Note: “ / ” in Table 1 means there is no corresponding preparation parameter.
[0055] Table 2
[0056] Note: “ / ” in Table 2 indicates no corresponding preparation parameters.
[0057] Table 3
[0058] Through visual observation, it can be seen that the magnesium aluminum spinel transparent ceramics prepared by the present application have no cracking phenomenon. In Tables 1 to 3, the size of magnesium aluminum spinel transparent ceramics Φ400mm×5mm means diameter 400mm×thickness 5mm, and the size 500mm×500mm×6mm means length 500mm×width 500mm×thickness 6mm, and the same applies to the others. In Tables 1 to 3, according to Examples 1-1 to 1-7, Examples 2-1 to 2-9, Examples 3-1 to 3-7, and Comparative Examples 1-1 to 1-2, it can be seen that the large-size magnesium aluminum spinel transparent ceramics prepared by the preparation method of the present application have good transmittance and good uniformity, and can significantly reduce the risk of ceramic cracking.
[0059] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for preparing a magnesium aluminum spinel transparent ceramic, comprising the following steps: S1. Raw material pretreatment, comprising: adding a sintering aid and an organic solvent to a magnesium aluminum spinel powder for ball milling, and then spray granulating to obtain a magnesium aluminum spinel spherical powder with an average particle size of 20-150 μm, wherein the mass percentage of the sintering aid is 0-0.5% based on the mass of the magnesium aluminum spinel powder, and the mass percentage of the organic solvent is 50-400%; S2. Vacuum hot pressing, comprising: vacuum hot pressing and sintering the spherical powder of magnesium aluminum spinel, the vacuum degree is 10 -1 -10 - 3 Pa, sintering temperature is 1300-1600℃, high pressure is 35-50MPa, low pressure is 15-25MPa, high and low pressure cycle pressurization is performed 2-8 times, high pressure insulation time is 10-30min, low pressure insulation time is 10-30min, and the total sintering time is 2-6 hours; pressure is released, the pressure is reduced to 0, and the temperature is reduced to 200-400℃ at a cooling rate of 2-5℃ / min, and then to room temperature to obtain a magnesia-alumina spinel sintered body; S3. Hot isostatic pressing, comprising: in an argon atmosphere, the temperature is 1600-1800°C, the pressure is 150-200MPa, the magnesium-aluminum spinel sintered body is kept hot and pressurized for 1-5 hours, then the temperature is reduced to 1100-1400°C at a cooling rate of 1-2°C / min, the temperature is kept for 5-20h for in-situ annealing, and then the temperature is reduced to room temperature at a cooling rate of 3-5°C / min to obtain the magnesium-aluminum spinel transparent ceramic.
2. The preparation method according to claim 1, wherein The ball milling includes a ball milling speed of 50-200 rpm and a ball milling time of 0.5-5 hours.
3. The preparation method according to claim 1, wherein The purity of the magnesia-alumina spinel powder is ≥99.9%.
4. The preparation method according to claim 3, wherein The purity of the magnesia-alumina spinel powder is ≥99.99%.
5. The preparation method according to claim 4, wherein The purity of the magnesia-alumina spinel powder is ≥99.999%.
6. The preparation method according to claim 1, wherein The particle size D50 of the magnesia-alumina spinel powder is 0.1-2 μm.
7. The preparation method according to claim 1, wherein The high and low pressure cycles are performed 2-6 times.
8. The preparation method according to any one of claims 1 to 7, wherein The sintering aid is selected from at least one of Y2O3, La2O3, LiF, NaF, CaO, and MgF2.
9. The preparation method according to any one of claims 1 to 7, wherein The organic solvent is selected from at least one of anhydrous ethanol and isopropanol.
10. A magnesium-aluminum spinel transparent ceramic prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Processing method for processing ceramic based on low-temperature resonance
CN121492196A
Hydro-thermal synthesis rod-like powder sintered magnesium aluminate spinel transparent ceramic and preparation method thereof
CN122325216A
Hydrothermal synthesis of sintered spinel transparent ceramics with rod-like powder and preparation method thereof
CN122325216B